2021
DOI: 10.1002/rmv.2320
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory‐based testing for hepatitis C infection using dried blood spot samples: A systematic review and meta‐analysis of diagnostic accuracy

Abstract: The use of dried blood spot (DBS) samples can facilitate the implementation of reflex testing by circumventing the need for centrifugation and freezing of venous blood samples. This systematic review assessed the accuracy of using DBS samples to diagnose chronic hepatitis C virus (HCV) infection. A comprehensive search was undertaken to identify articles published up to July 2020 evaluating the diagnostic accuracy of anti-HCV, HCV-RNA and HCV core antigen tests using DBS. Screening, data extraction, quality ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 109 publications
0
7
0
Order By: Relevance
“…Previous studies using DBS have demonstrated its reliability in detecting RNA, antibodies and drug resistance-associated substitutions. 2,9,10 The provision of such alternative diagnosis approaches to low-income, remote and hardto-reach populations may help close the gaps in eliminating HCV by 2030. Therefore, using DBS as an alternative means for genomic sequencing efforts could empower HCV surveillance initiatives and enable point-of-care genomic analysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies using DBS have demonstrated its reliability in detecting RNA, antibodies and drug resistance-associated substitutions. 2,9,10 The provision of such alternative diagnosis approaches to low-income, remote and hardto-reach populations may help close the gaps in eliminating HCV by 2030. Therefore, using DBS as an alternative means for genomic sequencing efforts could empower HCV surveillance initiatives and enable point-of-care genomic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, DBS specimens once completely dried are considered noninfectious and nonhazardous allowing them to be shipped and transported at ambient temperatures. Previous studies using DBS have demonstrated its reliability in detecting RNA, antibodies and drug resistance‐associated substitutions 2,9,10 . The provision of such alternative diagnosis approaches to low‐income, remote and hard‐to‐reach populations may help close the gaps in eliminating HCV by 2030.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The interassay accuracy and precision were less than 10% across a range of different hematocrit values ( 7 ). DBS technology is increasingly being recognized as a valuable alternative to plasma sampling ( 8 ) and is potentially used in different scenarios such as testing for hepatitis C infection ( 9 ) or monitoring of anticancer drugs ( 10 ), screening at-risk populations for various diseases ( 11 ), and general screening ( 12 ). The analytical part has similarly advanced from manual handling of DBS samples to a combination of liquid chromotography-tandem mass spectrometry ( 13 ) and robotic DBS extraction systems allowing a fully automated analytical process of DBS ( 14 ).…”
Section: Introductionmentioning
confidence: 99%